(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
Diabetes mellitus is a metabolic disorder affecting a great part of population around the world. It is the fifth leading death causing disease in the world and its cases are increasing day by day. Traditional medicine is thought to have promising future in the treatment of diabetes mellitus. In contrast to synthetic drugs phytochemicals are considered to be free from side effects. As one of the main class of natural products, alkaloids and their derivatives have been widely used as sources of pharmacological agents against a variety of medical problems. Many studies confirmed the role of alkaloids in the management of diabetes and numerous alkaloids isolated from different medicinal plants were found active against diabetes. Like other natural products, alkaloids regulate glucose metabolism either by inhibiting or inducing multiple candidate proteins including AMP-activated protein kinase, glucose transporters, glycogen synthase kinase-3, sterol regulatory element-binding proteins 1, glucokinase, glucose-6-phosphatase, acetyl-CoA carboxylase among the others. A comprehensive review of alkaloids reported in the literature with anti-diabetic activities and their target enzymes is conducted, with the aim to help in exploring the use of alkaloids as anti-diabetic agents. Future work should focus on rigorous clinical studies of the alkaloids, their development and relevant drug targets.